Managing knowledge assets, creativity and innovation - Leonard-Barton, Dorothy (Singapore : World Scientific, 2011)
'This book pulls together for the first time, works on knowledge and innovation, including the implementation of new processes and products, written by Dorothy A Leonard over more than two decades. It consists of articles from journals in diverse fields (e.g. the award-winning article on Core Capabilities and Core Rigidities) and book chapters that cover the innovation process, from its inception in peoples' heads to its implementation. An underlying theme running throughout the book is managing the flow of knowledge that propels innovation - especially tacit knowledge. Such knowledge is difficult to transfer or embody in a new product, process or service. However, it is not only essential but often comprises the most valuable component in the innovation. The opening chapter, written expressly for this volume, probes the connections between tacit knowledge, creativity and innovation'--Back cover.
Includes bibliographical references and index.
Keywords: Technological innovations -- Management; Technology transfer; Knowledge management